RANCANG BANGUN ALAT DETEKSI KEHADIRAN ORANG - Erlansyah, Deni; Wydyanto, Wydyanto (JURNAL ILMIAH MATRIK, 2016)
Abstract: Currently criminality condition has been greatly improved. This is due to lack of employment and the high prices of daily necessities that impact on increasing crime rate. Crime is not just happening on the streets, but also in housing. Many homes are visited by people who are not responsible, who then takes the valuables. This situation requires us to be more careful so as reduce the level of crime that occurs in housing projects. The solution is that we can create a tool that can detect the presence of people who do not want. How the tool works based microcontroller are as follows: 1) If there is a presence of people, then the sensor the presence of people going to work, 2) the sensor will send writing (text) to mobile phones via Bluetooth, 3) the sensor will also enable the system alarms. Keywords: Microkontroller, Sensor, Presence